Pre-Late Wisconsinan Paleoenvironments in Atlantic Canada - Mott, Robert; Grant, Douglas (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1985)
ABSTRACTNumerous Quaternary organic deposits of various lithologies beneath one or more till units of Wisconsinan age have been discovered in boreholes and exposures in coastal bluffs, quarries and river banks at widespread localities throughout Atlantic Canada. Ongoing palynological and macro-fossil studies, still in a preliminary stage at many sites, reveal a variety of environments from forests dominated by thermophilous hardwood genera and white pine, to mixed temperate hardwood and conifer forests, to boreal coniferous forests of spruce and balsam fir, and forest tundra and tundra communities characterized by spruce, shrubs and herbs. Lithologie and pollen stratigraphie relationships and radiocarbon, amino acid and Thorium/Uranium dating allow a tentative assignment to the Sangamonian Stage and possibly to Early and Middle Wisconsinan time. Three intervals of organic accumulation are apparent: an early interval, when climate became warmer than the present; a second interval, when climate was similar to the present; and a third interval, with cooler climate. The latter interval is characterized by at least three climatic cycles, each one cooler than the previous cycle. Tentative correlations with the deep-sea oxygen isotope record and continental palynological records are presented.